OBSERVASI PRODUKSI TANDAN BUAH SEGAR PADA PERKEBUNAN SAWIT RAKYAT - Riyanto, Riyanto (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2014)
The objective of this observation is to understand the trendof oil palm fresh fruit bunches (FFB)within one year and to observe the oil palm yield potential of small holder. The observation was held in one of small holder plantation located in Desa Sonomartani, Kecamatan Sukarame, Kabupaten Labuhan Batu Utara (north Sumatra). The palms were planted in shallow peat. The seedlings were assuming coming from illegitimate seeds. In general, like any other small holder palms, the farm was not well managed such as manuring was only applied ones per year with dosage 0.5 kg Urea. Weeding in palm circle and inter row is not totally cleaned. The observation was done during January to December 2013. The number of palms sampled is 238 palms or more or less one hectare. The stand trees in the area is 140 palms/ha. Average bunch weight during observation is average on 13 kg. Based on the observation, the trend of one year production was tent to distribute nearly in normal distribution.The yield potential is 21.8 ton FFB /ha/year. However, the actual yield was only around 9.9 ton FFB/ ha/ year. This actual production is still far lower from their potency. In order the yield achieve their potential, herewith some recommendation (i) The seeds planted much be certified seeds bought from legal seed producer, (ii), weeding must be done properly in which palm circle, harvesting path and inter-row must be free from any weed, (iii) manuring program must be correct dose, type, time and application. Drainage must be maintained to avoid water lagging. The palms are also must be kept from any pest & Disease attack and thief.